Report on Biopsy Collections from Specimens Collected from the Surrounds of the West Atlas Oil Leak - Fish Specimens - Gagnon, Marthe Monique (Department of Sustainability, Environment, Water, Population and Communities, 2009)
1. Skin swabs on four fish species did not indicate exposure to petroleum hydrocarbons. 2. Fish stomach contents indicate no ingestion of petroleum hydrocarbons. 3. Fish white muscle indicates no trace of petroleum hydrocarbons.4. During the oil spill, surface animals are more at risk of being affected by exposure to petroleum hydrocarbons than are deep sea fish. 5. It is imperative to commence a monitoring program of fish health during the oil spill, and continue monitoring after the oil leak has been solved.